The response of gut associated lymphoid tissues (GALT) following oral administration of P. multocida B2 in rats - Awang Hazmi Awang Junaidi.
A total of 12 adults, Spraque-dawley rats which were divided into groups (n=6) were used in this study. The study was aim to investigate the response of GALT following oral administration of P. multocida type B2. Six rats of the first group were given 0.5ml 10 CFU of P. multocida type B2 each via oral by using stomach tube, while another six rats in the second group (control) were given 0.5ml of normal saline using the same method. Following inoculation, the rats will kept for 2 weeks and given feed and water ad-libitum. After 2 weeks the rats were euthanised and microscopic macroscopic evaluations were performed on each section of intestines. Macroscopic evaluations revealed that there was no significance different (p>0.05) in the number and the length of the Peyer's patches of each part of the intestine between the control and infected groups. The width of Peyer's patches was significantly different (p<0.05) in control group as compare to infected group. Meanwhile, microscopic evaluation of the intestine revealed that the number of follicles in infected group slightly higher than the control group, however the different was not significant (p>0.05). The size (length and width) of lymphoid follicles and the number of intraepithelial lymphocytes (IEL's) were significantly (P<0.05) in infected group as compared to the control group. The number of plasma cells was also significantly (p<0.05) higher in the infected group as compared to control group. The present study demonstrated the significant morphological changes of Gut Associated Lymphoid Tissues (GALT) following oral administration of P. multocida B2 in rats.